Sørejser og historiografisk politik - Britisk historiefortælling om havet og dets folk - Heinesen, Johan (Slagmark - Tidsskrift for idéhistorie, 2018)
The article traces ways in which the historiography of British voyaging and exploration has configured the relationship between shipboard communities and words. This is argued to be a ‘political’ issue in the sense bestowed upon the word by Jacques Rancière. He sees the kernel of politics to be the struggle about speech and the ability of speaking beings to designate what is ‘common’ to community. Taking its clues from Rancière’s poetics of knowledge the article explores how historiography has dealt with the ship’s community of speaking beings. It identifies a strategy through which the narration of the ship distinguishes between good speech and bad speech and lets the former be the foundation of a proper community, while the later becomes a transgression of the boundaries of community. Historical science later supplemented this displacement of speech by tying the truth of community to hidden structures, thereby disabling the actor’s ability to narrate the common.